2003
DOI: 10.1097/01.tp.0000054839.43852.bf
|View full text |Cite
|
Sign up to set email alerts
|

Histocompatible miniature swine: an inbred large-animal model1

Abstract: Three herds of miniature swine, each homozygous for a different set of alleles at the major histocompatibility complex (MHC), and five intra-MHC recombinant strains, have been reported by the authors' laboratory. One herd (SLAdd) was selected for further inbreeding to achieve a histocompatible line. It has undergone seven additional generations of sequential brother-sister or father-daughter matings (termed G7). To determine the level of histocompatibility of these animals, the authors performed skin and heart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
69
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 7 publications
(10 reference statements)
0
69
0
Order By: Relevance
“…Preclinical functional studies using human umbilical cord tissue-derived cells (UTCs) are currently in progress, and early results show promise for these UTCs as cellular therapy of retinal disease in animal models. 16 Massachusetts General Hospital (MGH) MHC-defined miniature swine [17][18][19] provide a unique preclinical model to assess immunogenicity of allogeneic UTCs. By approximating donor-recipient mismatch barriers often seen in clinical transplantations, these animals have been used for large animal studies of cellular and solid organ transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical functional studies using human umbilical cord tissue-derived cells (UTCs) are currently in progress, and early results show promise for these UTCs as cellular therapy of retinal disease in animal models. 16 Massachusetts General Hospital (MGH) MHC-defined miniature swine [17][18][19] provide a unique preclinical model to assess immunogenicity of allogeneic UTCs. By approximating donor-recipient mismatch barriers often seen in clinical transplantations, these animals have been used for large animal studies of cellular and solid organ transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Although a few lines of inbred miniature pigs which express the homologous major histocompatibility complex (MHC) molecules exist (6,28), the majority of outbred conventional pigs harbor polymorphic MHC molecules on their cells. That is the primary reason that it has proven difficult to conduct a proper analysis of MHC-restricted T-cell immune responses in pigs immunized with vaccines or infected with the wild-type viruses.…”
mentioning
confidence: 99%
“…Similar to MHC-mismatched recipients, IFN-γ perfusion facilitated rejection in near-syngeneic recipients. Although there were minimal minor antigen differences in G8 animals (5), that may have been unmasked by the IFN-γ perfusion, the rapidity with which heart grafts were rejected suggests that antigen-independent mechanisms were responsible. Likewise, recent studies by El Sawy and colleagues showed that CD8+ memory T cells produced IFN-y within 48 hours after transplantation -and before T cell priming occurred -, which amplified an antigen-independent inflammatory response (7).…”
Section: Discussionmentioning
confidence: 99%